A Time-Varying Error Correction Model of Price Discovery: Implications for Portfolio Construction and Hedging - Hội thảo quốc tế Ngân hàng và Tài chính thế giới 2015 (Trường Đại học Kinh tế, 2020)
We propose a model of time-varying price discovery based on a rolling-window error correction framework. We show that price discovery in five commodities is dominated by the spot market, while, in only six commodities, price discovery is dominated by the futures market. We consistently discover that for 14 commodities price discovery is time-varying, which has implications for portfolio construction and hedging. Our findings, therefore, challenge the wellestablished view in commodity markets that it is the futures market which dominates the price discovery process